Sociology of Education and Dance Arts:Harmony in Madrasah Ibtidaiyah Minhajuttholibin - Ridwan, Ridwan; Riyanti, Riyanti; Rahmawati, Niken (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2025)
The sociology of education studies how social interactions and cultural contexts affect the learning process at Madrasah Ibtidaiyah Minhaajuttholibin. The purpose of the research is to find out the influence of dance on the social and emotional development of students in Madrasah Ibtidaiyah, Develop effective strategies to integrate dance arts in the Education curriculum, Assess the role of dance in preserving local culture and traditions among students, Build synergy between schools, parents, and communities to support arts programs in madrasas. This study uses a qualitative design with a case study approach. The research population consisted of students, teachers, and parents at Madrasah Ibtidaiyah Minhaajuttholibin. The sample was taken purposively, by selecting 30 students, 5 teachers, and 10 parents who were involved in dance arts activities in the madrasah. Data Collection through Interviews, Questionnaires, and Observations, conducted during dance activities to record student interaction and participation. Implementation Steps: Prepare research instruments and obtain approval from the madrasah. Conduct interviews with students, teachers, and parents on a scheduled basis. Distribute questionnaires to students and collect data. Conducting observations during dance activities in class. Qualitative Analysis: Data from interviews and observations will be analysed using thematic analysis techniques to identify patterns and themes. Quantitative Analysis: Data from the questionnaire will be analysed using descriptive statistics to describe students' attitudes towards dance. The results of this study found that involvement in dance can strengthen the relationship between students, teachers, and parents, creating a more harmonious learning environment. This study successfully identified the impact of dance on the social and emotional development of students at Madrasah Ibtidaiyah, showing that dance can improve their social skills. However, this study has limitations in terms of a limited sample size and focus on only one madrasah, so the results may not be fully generalizable.